2017
DOI: 10.1117/12.2254132
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral image processing for detection and grading of skin erythema

Abstract: Visual assessment is the most common clinical investigation of skin reactions in radiotherapy. Due to the subjective nature of this method, additional noninvasive techniques are needed for more accurate evaluation. Our goal is to evaluate the effectiveness of hyperspectral image analysis for that purpose. In this pilot study, we focused on detection and grading of skin Erythema. This paper reports our proposed processing pipeline and experimental findings. Experiments have been performed to demonstrate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…This technology allows the user to select specific wavelength to assess the presence of melanin and haemoglobin, as well as performing nCDA of the overall dark circle area. 17 Some published articles have already highlighted the benefit of this technique to assess skin colour, 18 and even more specifically, skin pigment, 19 erythema, 20 melanin, total haemoglobin and oxygen saturation in dark circles. 21 The multispectral analysis performed in this research showed a higher melanin index that suggests hyperpigmentation, and a higher haemoglobin index that supports the hypothesis of blood vessel dilation in the dark circles area.…”
Section: Discussionmentioning
confidence: 99%
“…This technology allows the user to select specific wavelength to assess the presence of melanin and haemoglobin, as well as performing nCDA of the overall dark circle area. 17 Some published articles have already highlighted the benefit of this technique to assess skin colour, 18 and even more specifically, skin pigment, 19 erythema, 20 melanin, total haemoglobin and oxygen saturation in dark circles. 21 The multispectral analysis performed in this research showed a higher melanin index that suggests hyperpigmentation, and a higher haemoglobin index that supports the hypothesis of blood vessel dilation in the dark circles area.…”
Section: Discussionmentioning
confidence: 99%
“…[32,33] The Visual Assessment (VA) declares the erythema regions through the X-OR correlation to produce the corrected images. [34] The performance evaluation was analyzed by the contradiction of colored digitalized images Red-Green-Blue (RGB) pigments. The [6] Hyper Spectral Images (HSI) and the RGB pigments are analyzed and classified via the smoothing of images by a low pass filter called Savitzky-Golay and the results are compared with colored images.…”
Section: Erythema Migransmentioning
confidence: 99%
“…This combination produces a three-dimensional data format. 18,19 This data includes two-dimensional spatial information along a third spectral dimension to form a datacube. The datacube's spatial information is contained in an image of the object, and its spectral information is included in capturing the same image using a sequence of spectral bands.…”
Section: Introductionmentioning
confidence: 99%